PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN LAPTOP PADA CV. ABONE KOMPUTER DI TELUK KUANTAN - Wicara, Dinda Genta; Indra, Ayura (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at CV. Abone Computer Teluk Kuantan. The Population of this research are the consumers who bought laptop at CV. Abone Computer Teluk Kuantan as many as 536 consumers. Samples taken are based on the method uses slovin formula that is 84 respondents. The Method of data collection uses interviews and questionnaires. Hypothesis testing uses multiple linier regression analysis method with result Y = -0,281 + 0,105X1 + 1,388X2 + 0,136X3-0,02X4. This research can be done with several analysis that is based on t test which shows that partially advertising variable, sales promotion, public relation, direct marketing, influence to the purchase decision at CV. Abone Computer Teluk Kuantan. Furthermore, based on simultaneous test (F test) known independent variable influence dependent variable where the value of Fcount (166,569) <Ftabel (2,49) with sig (0,000) <0,05. While based on the calculation of Coefficient Determination (R2) value obtained Adjusted R Square value of 0.889. This shows that advertising, sales promotion, public relations, direct marketing gives an effect of 88.9% of the purchase decision at the CV. Abone Komputer Teluk Kuantan, while the remaining 11.1% is influenced by other variables that are not examined in this research